Protecting traditional cultural food practices: Trends in diet quality and intake of ultra-processed foods by Indigenous status and race/ethnicity among a nationally representative sample of adults in Canada - Dana Lee Olstad; Sara Nejatinamini; Rosanne Blanchet; Jean-Claude Moubarac; Jane Polsky; Lana Vanderlee; Katherine M. Livingstone; Seyed Hosseini Pozveh (Elsevier, 2023)
Background: The traditional cultural food practices of Indigenous people and adults from racial/ethnic minority groups may be eroded in the current food system where nutrient-poor and ultra-processed foods (UPF) are the most affordable and normative options, and where experiences of racism may promote unhealthy dietary patterns. We quantified absolute and relative gaps in diet quality and UPF intake of a nationally representative sample of adults in Canada by Indigenous status and race/ethnicity, and trends between 2004 and 2015. Methods: Adults (≥18 years) in the Canadian Community Health Survey-Nutrition self-reported Indigenous status and race/ethnicity and completed a 24-h dietary recall in 2004 (n = 20,880) or 2015 (n = 13,970) to calculate Healthy Eating Index-2015 (HEI-2015) scores from 0 to 100 and proportion of energy from UPF. Absolute and relative dietary gaps were quantified for Indigenous people and six racial/ethnic minority groups relative to White adults and trends between 2004 and 2015. Results: Adults from all six racial/ethnic minority groups had higher mean HEI-2015 scores (58.7-61.9) than White (56.3) and Indigenous adults (51.9), and lower mean UPF intake (31.0%-41.0%) than White (45.9%) and Indigenous adults (51.9%) in 2015. As a result, absolute gaps in diet quality were positive and gaps in UPF intake were negative among racial/ethnic minority groups-indicating more favourable intakes-while the reverse was found among Indigenous adults. Relative dietary gaps were small. Absolute and relative dietary gaps remained largely stable. Conclusions: Adults from six racial/ethnic minority groups had higher diet quality and lower UPF intake, whereas Indigenous adults had poorer diet quality and higher UPF intake compared to White adults between 2004 and 2015. Absolute and relative dietary gaps remained largely stable. Findings suggest racial/ethnic minority groups may have retained some healthful aspects of their traditional cultural food practices while highlighting persistent dietary inequities that affect Canada's Indigenous people.